PENUNJUKAN TANAH DAN BANGUNAN SEBAGAI JAMINAN PELUNASAN UTANGPADA PEMBIAYAAN BERDASARKAN PRINSIP SYARIAH - Setyorini, Dyah (Universitas Trisakti, 2025)
As is known, financing institutions with sharia principles have shown extraordinary growth in Indonesia. In practice, financing based on sharia principles is often understood by some people as interest-free and collateral-free financing. This opinion is not entirely correct because not applying interest is correct but not requiring collateral is incorrect, even though several financing institutions with sharia principles provide financing by providing relief regarding collateral. Financing institutions with sharia principles are the embodiment of an Islamic economy that prioritizes sharia principles, including material guarantees. Guarantee institutions for immovable objects (land and buildings) are operationalized using guarantee institutions according to positive Indonesian law, namely Law Number 4 of 1996 concerning Mortgage Rights for Land and Objects Related to Land (UUHT), where the principles of Mortgage Rights in UUHT do not conflict with the pillars and conditions for material guarantees in Islamic law (ar-rahn). This also means that the execution is also subject to the provisions of the Mortgage Rights. However, the majority of people think that when financing using sharia principles, guarantee institutions are used according to Islamic law. This is where there is a need to increase socialization regarding guarantee institutions using sharia principles and for the government to immediately formulate laws and regulations that specifically regulate the execution of mortgage rights because so far the execution through auction sales in the UUHT has been carried out according to Article 224 HIR (258 RBg) as stipulated in Article 26 UUHT and its explanation.